2013
DOI: 10.1111/ene.12249
|View full text |Cite
|
Sign up to set email alerts
|

Limbic encephalitis: a clinical‐radiological comparison between herpetic and autoimmune etiologies

Abstract: There are few differences between HE and AE. Psychiatric symptoms and association with tumors were unique for AE. Acute onset with fever and absence of basal ganglia involvement in magnetic resonance imaging support a diagnosis of HE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 10 publications
3
54
1
3
Order By: Relevance
“…As well, involvement of the basal ganglia, thalamus, and (orbital) frontal lobe may appear; our series changes were even bilateral in 53 % of patients (Chow et al 2015;Domingues et al 1998;Oyanguren et al 2013;Sili et al 2014). Our study suggests the superiority of DWI to conventional T2-or FLAIR-weighted MRI in detection of early signal abnormalities in HSVE (Renard et al 2015).…”
Section: Mri Imagingsupporting
confidence: 52%
See 1 more Smart Citation
“…As well, involvement of the basal ganglia, thalamus, and (orbital) frontal lobe may appear; our series changes were even bilateral in 53 % of patients (Chow et al 2015;Domingues et al 1998;Oyanguren et al 2013;Sili et al 2014). Our study suggests the superiority of DWI to conventional T2-or FLAIR-weighted MRI in detection of early signal abnormalities in HSVE (Renard et al 2015).…”
Section: Mri Imagingsupporting
confidence: 52%
“…This may be of particular importance especially in cases with initial normal CSF and missing systemic inflammatory signs. Nevertheless, MRI may even be repeatedly negative in PCR-based HSVE (Hollinger et al 2000;Sheybani et al 2013) even when DWI imaging was performed (Oyanguren et al 2013). In our study, 2/15 HSV patients remained negative in MRI imaging including DWI in one patient (done on second day after onset of symptoms).…”
Section: Mri Imagingmentioning
confidence: 44%
“…10 In addition, even though both HSE and LE involve the TL, basal ganglia involvement on MR imaging favors nonherpetic etiologies. 12 It has been demonstrated that some types of viral encephalitis can trigger autoimmune LE, 53,54 particularly anti-Nmethyl-D-aspartate receptor encephalitis. 55 This phenomenon occurs when prolonged or atypical neurologic symptoms recur after successful control of the viral infection.…”
Section: Infectious Lementioning
confidence: 99%
“…In addition, symptoms can precede the diagnosis of cancer, and T2/FLAIR hyperintensity in the medial aspect of the TL may mimic several other disorders. [4][5][6][7][8][9][10][11][12] MR imaging plays a key role in the management of patients with suspected LE and is used as part of the LE diagnostic criteria to rule out differential diagnoses. Certain imaging and clinical peculiarities may narrow the list of possible diagnoses; however, a complete list of differential diagnoses remains beyond the scope of this article.…”
mentioning
confidence: 99%
“…While limbic dysfunction is the single most consistent finding in autoimmune encephalitis, varying degrees of involvement are seen within the neocortex, striatum, hindbrain, spine, and peripheral nervous system based on the unique antibody profile. 3,[9][10][11][12] In addition, certain antibody subtypes consistently lack imaging manifestations, while others characteristically demonstrate prominent "extralimbic" involvement. 3,7,[13][14][15] Although it was initially thought to be relatively rare, there is growing consensus that autoimmune encephalitis is responsible for a subset of altered mental status previously considered idiopathic.…”
mentioning
confidence: 99%